Photovoltaic ground fault detection recommendations for array safety and operation. (15th December 2016) - Flicker, Jack; Johnson, Jay
Highlights: Examined ground faults in PV arrays and the efficacy of fuse, RCD/CSM, and Riso protection devices. Decreasing fuse ratings below 1 A does not improve fault detection due to GFPD resistances. Sandia partnered with an EPC firm toeliminate fire risk in PV systems through RCD protection. To set CSM/RCD thresholds, a 70 W fault should be used to derive a trip-time vs. fault current curve. Theoretical equations for Riso were derived for arrays to determine trip thresholds. Any a priori Riso trip thresholdcannot mitigate both fire and unwanted tripping for all arrays. Abstract: PV faults have caused rooftop fires in the United States, Europe, and elsewhere in the world. One prominent cause of past electrical fires was the ground fault detection "blind spot" in fuse-based protection systems discovered by the Solar America Board for Codes and Standards (Solar ABCs) steering committee in 2011. Unfortunately, while a number of alternatives to ground fault fuses have been identified, there has been limited adoption or historical use of these technologies in the U.S. Analytical and numerical SPICE simulations were conducted for a wide variety of ground faults and array configurations to understand the limitations of fuse-based ground fault protection in PV systems and determine proper trip settings for alternative GFPDs. Simulation results were compared with experimental measurements on arrays to validate the SPICE model as well as provide direction on proper thresholding of residual current detector (RCD), current sense monitor (CSM) and isolation monitor (Riso ) devices based on historical fault current data. We argue the combination of simulation results with historical data indicates robust settings are possible for each of these technologies to minimize unwanted tripping events while maximizing PV fault detection.